THE INFLUENCE OF CORPORATE GOVERNANCE AND CSR ON DIVIDEND POLICY WITH LIQUIDITY AS A MODERATION VARIABLE IN LQ45 INDEX COMPANIES - Putri, Aisyah Desravi; Nur, Dhani Ichsanuddin; Khoirotunnisa, Fani (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
This study was conducted with the aim of determining the contribution of corporate governance and corporate social responsibility to dividend policy with liquidity as a moderating variable. The population in this study were LQ45 index companies listed on the IDX for the period 2019-2023. The method used to determine the sample in this study was the purposive sampling method. Through this method, 11 companies were obtained that could be observed during the period 2019-2023 (5 years) so that the total observation data in this study was 55 data. The analysis technique used in this study was Moderated Regression Analysis (MRA) with the help of the SPSS 25 analysis tool. The results of the study explain that corporate governance contributes positively to dividend policy, while corporate social responsibility does not contribute to dividend policy. Liquidity contributes to weakening the relationship between corporate governance and dividend policy, while for the relationship between corporate social responsibility and dividend policy, liquidity cannot contribute